Hydrogeologic characteristics of groundwater in the Kızılırmak graben (Nevşehir–Turkey) and its evaluation in terms of irrigation water quality - Ramazan Demircioğlu; Yusuf Gökhan Dursun; İlknur Demircioğlu (Water Supply, 2023)
In this study, an area of 150 km2 with important settlements and agricultural areas within the Kızılırmak and Kuyulukışla grabens, in the north of Nevşehir province (Turkey), was investigated. This study aimed to evaluate the hydrochemical properties and water quality of the vital groundwater in the study area, determine effective utilisation methods, and make recommendations for sustainable use. From the data obtained as a result of these analyses, sodium adsorption ratio (SAR) and sodium percentage (%Na) values were calculated and compared with WHO (World Health Organization) and TS-266 (Turkish Standards) quality standards to determine the characteristics of water for human consumption and irrigation for agricultural purposes. Based on these values, Wilcox diagrams and US Salinity Laboratory diagrams were used. According to these evaluations, it was found that sample SMP1 is not suitable for use as drinking water according to the basic parameters in the reference standards, while the other samples are suitable for drinking and human consumption. Electrical conductivity, %Na, SAR values, US Salinity Laboratory, and Wilcox diagrams were used to evaluate the use of water resources for irrigation purposes. According to the results obtained, all samples except sample SMP1 were found to be suitable for use as irrigation water. HIGHLIGHTS Kızılırmak graben (Nevşehir–Central Anatolia–Turkey) and evaluation of water quality.; Groundwater samples were analysed for their suitability as drinking and irrigation water.; Calculation to determine the characteristics of irrigation water use for agricultural purposes.;